BUDIDAYA TERNAK BABI BALI DI DESA BONGKASA PERTIWI BADUNG SEBAGAI SOLUSI PENINGKATAN PRODUKTIVITAS DAN PENCEGAHAN WABAH PENYAKIT ASF - I Dewa Putu Juwana; I Gusti Ayu Rai; I Gusti Agung Gede Wiadnyana (LP3M Universitas PGRI Mahadewa Indonesia, 2025)
Bongkasa Pertiwi Village, Abiansemal District, Badung Regency, is a highland area where the community maintains strong traditions, including raising Balinese pigs for both traditional and economic purposes. Balinese pigs have a genetic advantage in the form of high fat content, making them highly sought after as raw material for suckling pigs. However, since late 2021, pig farming in Bali has faced a serious threat in the form of an African Swine Fever (ASF) outbreak, which has caused mass deaths with a mortality rate of nearly 100%. This situation is exacerbated by the lack of understanding among farmers regarding disease prevention and management. This Community Service Program was implemented to address two main issues: (1) preventing the spread of ASF, and (2) developing Balinese pig fattening. The activities included outreach, training, mentoring, and the implementation of biosecurity practices in the barn. Additionally, training was provided on formulating high-fat, low-fiber feed to support optimal fattening. The results of this activity demonstrated improved knowledge and skills among farmers in implementing biosecurity measures, such as routine disinfection, pen waste management, and livestock movement restrictions. Farmers were also able to practice producing alternative feed based on local ingredients with a nutritional composition tailored to the needs of fattening Bali pigs. The resulting impacts included a reduced susceptibility to ASF, an average 12–15% increase in daily pig weight during the fattening period, and increased collective awareness among livestock groups for more professional business management. Thus, this activity not only provides a short-term solution to the ASF threat but also encourages the independence and sustainability of livestock groups in increasing Bali pig productivity, ultimately contributing to the economic resilience of village communities.